E FILLING ADOPTION AND TAX COMPLIANCE: A STUDY OF GENERATION Z THROUGH THE FIVE CONSTRUCTS OF THE TECHNOLOGY ACCEPTANCE MODEL - Putri, Eskasari; Elfreda, Khanzanorra (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2026)
This study aims to examine the factors that influence the adoption and acceptance of e-Filing among Generation Z taxpayers using the five constructs of the Technology Acceptance Model (TAM), including perceived ease of use, perceived usefulness, attitude toward use, behavioral intention to use, and actual system use (taxpayers’ compliance). The determination of sample size in this study refers to Roscoe (1976), who suggests that an appropriate sample size for multivariate research ranges from 30 to 500 respondents. This study applies a quantitative approach, with primary data collected through an online questionnaire distributed to 250 active registered taxpayers. Data were processed and analyzed using the PLS-SEM method with SmartPLS version 3. The results showed that Perceived Ease of Use (PE) has a significant effect on Perceived Usefulness (PU). Perceived Ease of Use (PE) and Perceived Usefulness (PU) positively influence Attitude Toward Use (ATU), which then has a positive effect on Behavioral Intention to Use (BI). Finally, Behavioral Intention to Use (BI) positively affects Actual System Use (KWP), reflected by taxpayer compliance in using e-Filing. The implication of this study is that both the Directorate General of Taxes (DGT) and related practitioners in charge of making tax policies should not focus only on administrative efficiency, but also consider Generation Z’s characteristics as Digital Natives, as this demographic segment has the potential to improve tax compliance and increase national state revenue.